Meeting students at their points of departure: prior knowledge, transfer, and first-year composition - Hegyi, Kevin, author; Doe, Sue R., advisor; Palmquist, Mike, committee member; Gingerich, Karla, committee member (Colorado State University. Libraries, 2021)
First-Year Composition students bring with them a vast supply of prior knowledge that influences their expectations for the outcomes of a First-Year Composition course. Composition faculty also bring with them an even greater wealth of prior knowledge that informs their expectations for the outcomes of First-Year Composition. This study sought to explore the intersection between First-Year Composition students and faculty in terms of their beliefs about writing and their expectations for the outcomes of the First-Year Composition course at the beginning of the semester. The goal of studying this inflection point involves consideration of how faculty engage and develop the prior knowledge of students through a rhetorical approach to writing in order to aid in transfer of learning from the course into students' academic, personal, public, and professional lives. Beliefs and attitudes of faculty and students were explored through a three-phase qualitative study involving surveys and interviews in order to gain clarity regarding the complex interaction of these two subject groups. Results indicate that faculty and students have different expectations for the First-Year Composition course, and these expectations are influenced by the different contexts each group is situated in. Composition faculty and WPAs should consider the First-Year Composition classroom as a complex "Teaching and Learning Situation" in order to meaningfully engage and develop the prior knowledge students bring with them to the course and to ensure the transfer of learning to future contexts.